Website Development and Search Engine Optimization - Anushri, D; Nandhini, M; Shanmugapriya, T (International Journal of Computer Sciences and Engineering, 2019)
Search Engine Optimization is a methodology of techniques that are used to increase the traffic of the website through the search results. It is also a method of finding the worth of the pages on the website. The main purpose of the online presence of the website is to get viewed by all over the world. The website which scores a high rank in the SEO results makes number of people to visit the site. Google provides the most user-friendly features for indexing the website. In this project, a simple website is developed and this website is indexed in Google. Various methods are used for the search engine process. Section I contains the introduction of this project, In Section II, the explanation of the project is included. In Section III, the various processes of SEO are included and Section IV contains the Conclusion.